An overview on the intellectual properties of the Fisheries Research Institute, Department of Fisheries, Malaysia - Ramli, Liyana; Md Noordin, Wan Norhana (Academica Press Solutions, 2024)
Intellectual creation, namely inventions, designs, literary works, artistic works, symbols, names, images, computer code, etc. is commonly relates to Intellectual property (IP). IP is one of the significant outputs of the research institution including at the Fisheries Research Institute (FRI), Department of Fisheries Malaysia. Awareness on IP generation and registration were only initiated in 9th Malaysian Plan (2006-2010) and starting from 10th Malaysia Plan (2011-2015), IP generation is one of the KPI that needs to be achieved by the FRI. Until March 2024, a total of 55 R&D innovations have been registered as IPs in various categories such as patents (11), utility innovations (10), trademarks (8) and copyrights (24) and 40 of them has been granted. For the past 15 years, the FRI has made provisions in generating and facilitate IP registration with the aim of getting them commercialized to help boosting the fisheries industries in Malaysia. There are great deals remain to be done particularly on establishing a comprehensive and specific internal IP strategy to help FRI in identifying and protecting the IPs, manage risks, promote IPs and, most importantly, generate and grow revenue.